The Efficacy of Piper betle L. (betel vine) Essential Oil against Malassezia pachydermatis Isolated from Skin Lesions of Canine Dermatitis - Aiemsaard, Jareerat; Papirom, Pittaya; Likitchatpakdee, Setthat; Thongkham, Eakachai (Journal of Mahanakorn Veterinary Medicine, 2020)
Resistance to antifungal drugs is a very important problem in the treatment of yeast infections in dogs. Therefore, it is important to study new substances to promote the treatment of Malassezia dermatitis in dogs. The aim of this study was to evaluate the antifungal activity of betel vine essential oil against Malassezia pachydermatis isolated from skin lesions of canine dermatitis by broth microdilution method and time kill test. The essential oil was analyzed for its chemical properties by gas chromatography/mass spectrometry (GC/MS). The GC/MS analysis revealed that eugenol was the major component of the tested betel vine essential oil (32.82%) followed by eugenol acetate (26.51%), 4-allyl-1,2-diacetoxybenzene (15.85%) and p-chavicol (7.45%). The results of antifungal testing demonstrated that betel vine essential oil had high antifungal activity against all tested M. patchydermatis isolates, with minimum inhibition concentration (MIC) and minimum fungicidal concentration (MFC) values equal to 0.66 and 0.66-1.13 µg/ml, respectively. The time-kill assay showed that a concentration of 8 times the MIC had the highest activity followed by 4 times the MIC, which eradicated tested microorganisms within 30 minutes by more than 99.9% and 90%, respectively. These activities appear to be dependent on dose and time and might be affected by the chemical constituents. These results revealed that betel vine essential oil has the potential to be developed as a drug for use against M. pachydermatis. Further studies to determine the suitable concentration and formulation, and for in vivo antifungal efficacy are required.